Culture Smart! Malaysia - King, Victor T. (London : Kuperard ; New York : Distributed in the United States and Canada by Random House Distribution Services, 2008)
Culture Smart provides essential information on attitudes, beliefs and behavior in different countries, ensuring that you arrive at your destination aware of basic manners, common courtesies, and sensitive issues. These concise guides tell you what to expect, how to behave, and how to establish a rapport with your hosts. This inside knowledge will enable you to steer clear of embarrassing gaffes and mistakes, feel confident in unfamiliar situations, and develop trust, friendships, and successful business relationships.
Land and people -- Values and attitudes -- Religion and festivals -- Meeting the Malaysians -- The Malaysians at home -- Time out -- Travel, health, and safety -- Business briefing -- Communicating.
"A quick guide to customs & etiquette"--Cover.
Includes index.
Includes bibliographical references (page 165) index.
Keywords: Malaysia -- Social life and customs; Malaysia -- Description and travel; Etiquette -- Malaysia